Hubungan antara tahap penglibatan aktiviti fizikal dengan tahap indeks jisim badan murid perempuan semasa pandemik COVID-19 - Abd Razak, Mohd Radzani; Abdul Aziz, Noraziera; Ismail, Erwan (Secholian Publication, 2022)
The goal of this study was to explore the association between physical activity levels and body mass index (BMI) among rural female students in the Rembau district, Negeri Sembilan during the COVID-19 pandemic. The instrument used in this study was Global Physical Activity Questionnaire (GPAQ) by (WHO, 2002) which was modified according to the suitability of the study. Female students aged 16 to 17 years were included in the study population and the total study sample size was 312 students. According to the BMI level, students are 69.2 percent normal weight,with a mean = 21.56kgm-2. Additionally, Pearson correlation analysis revealed no significant link between students' level of physical activity and their BMI values; r = 0.019; p > 0.05 = 0.732. During the COVID-19 pandemic, the physical activity involvement of rural female studens in the Rembau region did not influence on their BMI levels. Physical activity involvement at an early age is critical for maintaining good health and decreasing the risk of non-communicable diseases. Schools, alongside the physical education and health education teachers must develop programmes that can encourage students to participate in physical activity more actively during the COVID-19 pandemic.